Aryliminophosphoranes as Key Intermediates in the One-Pot Synthesis of 1-Aryl-1,3-dihydro-2H-benzimidazol-2-ones from N-Aryl-2-nitrosoanilines and Carbon Dioxide under Mild Metal-Free Conditions - Łukasik, Emilia; Wróbel, Zbigniew (Synthesis, 2016)
A new and convenient protocol is presented for the synthesis of 1-arylbenzimidazol-2-ones by a one-pot reaction of N-aryl-2-nitrosoanilines using solid carbon dioxide as a source of the key carbonyl moiety. The metal-free process is carried out under mild conditions and is compatible with a variety of substituents. The atom economy of the synthesis of the starting nitrosoanilines, accomplished by substitution of hydrogen, makes the entire synthesis of the target compounds environmentally friendly.
Keywords: annulations; heterocycles; cyclizations; nitroso compounds; fused-ring systems